Tuna skin gelatin production: optimization of extraction steps and process scale-up - Montero Barrantes, Manuel (2020)
Advantages of fish gelatin production include reduction of environmental impacts from waste, improved functionality, and fewer socio-cultural constraints. The extraction of gelatin from Yellowfin tuna (Thunnus albacares) skin was optimized using response surface methodology. Conditions for acid pretreatment (acetic acid concentration and treatment time) had a significant effect (p < 0.05) on the response variables skin hydration, gelatin extract, gel strength, and gel pH. Conditions for the extraction step (treatment temperature and treatment time) had a significant effect (p < 0.05) on the response variables gelling temperature, melting temperature, and gel strength. Process conditions affected the gel properties, and some effects were confirmed by evaluating the molecular weight profile of extracted proteins obtained through SDS-PAGE. The feasibility of the general extraction process scale-up was evaluated by comparing process yields and characteristics of gelatins, obtained at laboratory and pilot plant scales (scale-up ratio 80:1).